CHARACTERISTICS OF THE SCINTIGRAPHY WITH 99mTc- PERTECHNETATE IN PATIENTS WITH DIFFERENTIATED THYROID CARCINOMA - Nikolić, Katarina D; Vlajković, Marina (Medicinski podmladak, 2019)
Introduction: Differentiated thyroid carcinoma (DTC) derived from follicular cells is the most frequent endocrine malignancy, which most commonly occurs in patients with thyroid nodules.Aim: The aim of this retrospective analysis is to examine the type of scintigraphic finding of the thyroid gland obtained with 99mTc-pertechnetate in patients with DTC before tireoidectomy.Material and methods: Medical documentation comprised of 95 subjects with presurgical evaluation of thyroid nodules, including 18 men (51.5 ± 8.7 years old, range 43-68) and 77 women (48 ± 12, range 14-72 years). Other tests performed during the preoperative tests are the following: ultrasound examination of the thyroid gland, thyrotropin and thyroglobulin concentration measurement.Results: During the preoperative evaluation, thyroid ultrasound was performed in 20 (21%) out of 95 subjects with DTC, while 99mTc-pertechnetate scintigraphy was performed in 75 (79%) of patients, in addition to a clinical examination. What is the distribution of scintigraphic finding? Significantly, the highest incidence of DTC was found in the multinodular goiter: 61 (64%) subjects were diagnosed with this type of DTC, while 31 (33%) carcinomas were found in abnormal, solitary ”cold” nodules. The most frequent histopathological finding amongst nodules and multinodular goiter detected by scintigraphy was papillary thyroid carcinoma. Thyroid carcinoma was found in two patients with Graves’ disease and in one patient with a normal scintigraphic finding. The values of thyroid hormones were normal in 71% of DTC and elevated in fewer cases (21%). The ultrasound examination showed high-risk features in only 18 subjects (19%). Conclusion: Our results have shown that DTC is the most common finding in the multinodal goiter, and that it occurs much less often within the “cold” thyroid nodules. In a small percentage of subjects, thyroid neoplasm was found in patients with hyperthyroidism. The results of the study showed that thyroid gland scintigraphy with 99mTc-pertechnetate still has a significant diagnostic role in the examination of thyroid nodules.